Pemberdayaan Masyarakat terhadap Sampah dan Alat Pembakaran Sampah Minim Asap (Rocket Stove) di Tanjung Kertang - Rusiah Rusiah; Rosi Novita Ulfa; Said Zamri; Santi Pratama Anggraini; Sakina Aulia; Multi Sari; Miftakhul Maghfiroh; Muhammad Naufal Alafif; Riri Novitrianty; Norma Indah Magdalena Panjaitan; Aang Yudho Prastowo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The waste problem in Tanjung Kertang remains a serious environmental issue, mainly because some people dispose of waste directly into the sea due to limited access to landfill services. To address this problem, the KKN students of Universitas Maritim Raja Ali Haji carried out a community service program by constructing a Rocket Stove as an alternative for more environmentally friendly waste management. Rocket Stoves are a simple, locally sourced technology that can produce efficient combustion with low smoke emissions, making them relevant for use at the community level. The activity was carried out over a month in three stages: preparation (field observation, interviews, and coordination), implementation (preparation of tools and materials, and construction of the Rocket Stove), and evaluation (testing, socialization of use, and sustainability assessment). The results of the activity showed a positive response from the community with a fairly high level of participation, both in the construction process and in the dissemination of information on its use. This program not only helped reduce the volume of waste and reduce air pollution, but also increased the community's understanding and awareness of maintaining coastal environmental cleanliness.